Optimizing Network Controllability with Minimum Cost - Xiao Wang; Linying Xiang (Complexity)
In this paper, the issue of optimally modifying the structure of a directed network to guarantee its structural controllability is investigated. Given a directed network, in order to obtain a structurally controllable system, a framework for finding the minimum number of directed edges that need to be added to the network is proposed. After we get these edge-addition configurations, we further calculate the network cost of each optimization scheme and choose the one with the minimum cost. Our main contribution is twofold: first, we provide an algorithm able to find all optimal network modifications in polynomial time; second, we provide a way to calculate the cost of optimizing the network based on the node betweenness. Numerical simulations are given to illustrate the theoretical results.